USHUL FIQIH DIALECTICS ON CHILDFREE IN INDONESIAN SOCIETY - Septiana, Intan (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
Childfree in Indonesia is a new and further phenomenon because of a diversity of opinions that arise such as in terms of social society and the implementation of its laws. It affects values changes in childfree actors and social communities to have children. The essence of marriage to have children is a symbol of the happiness of a family and the sustainability of its offspring. The purpose of this study is to analyze how childfree can develop in Indonesia and how the legal validity is in the perspective of ushul fiqih. The theory of legal discovery used is Saddu az-Dzariah. Saddu az-Dzariah is to forbid something that the source may not be allowed. So that the emergence of childfree as a result of the development of increasingly advanced technology, such as social media affects changes in the mindset of the community to become freer without a filter on information from outside. In the childfree phenomenon that occurred in Indonesia, several influencers and artists began to publish their choice to do childfree. With this action, it seems to be a demonstration to do childfree. So that people who choose to be childfree are increasingly emerging, such as with the existence of childfree groups on various social media, it is feared that if more and more people choose childfree, there will be a childfree trend that will be followed by people without paying attention to the impact in the future. Furthermore, if you look at the study of ushul fiqih childfree containing mafsadat which results in damage, due to the non-fulfillment of one of the purposes of marriage, namely having children, then with saddu az-DZari'ah it becomes forbidden because it can cause a generational disconnection or inconsistency with maqasid Sharia.